Femoroacetabulární impingement syndrom - první zkušenosti s chirurgickou léčbou - Chládek, Petr; Musálek, Martin; Zahradník, Petr (Acta chirurgiae orthopaedicae et traumatologiae Čechoslovaca, 2014)
PURPOSE OF THE STUDY: Femoroacetabular impingement syndrome (FAI) represents a mechanical conflict between acetabulum and proximal part of the femur. This disorder may gradually result in the development of the hip osteoarthritis. FAI may be caused by an acetabular retroversion, rarely by coxa profunda or by asphericity of the femoral head and missing femoral head-neck offset respectively. However, a combination of both conditions is the most frequent. Before FAI treatment was adopted as a standard technique for hip preservation at our department, detailed cadaver studies of the vascular anatomy of the hip were performed and the relevant literature was reviewed. The aim of this study was to assess the efficiency of hip preserving surgery in relation to the technique used. We hypothesized that surgical intervention helped to alleviate pain and improve hip function. MATERIAL AND METHODS: In the period from October 11, 2005 to June 30, 2012, a total of 168 patients (190 hips) had surgery for FAI. After we met exclusion criteria, 83 hips were treated by surgical hip dislocation (SHD) and 17 undergoing anterior minimally invasive surgery (AMIS). The minimum follow-up was 12 months, with an average of 3 years and 4 months, and a range of 12 months to 7 years and 8 months. The subjective evaluation by the patients and the functional hip assessment were based on the Western Ontario and McMaster Universities Arthritis Index (WOMAC) and the non-Arthritic Hip Score (nAHS) questionnaires. To assess the efficiency of the techniques, the pre- and post-operative scores were compared in each group (SHD group, n=83; AMIS group, n=17). A comparison of pre- and post-operative data was also made for the groups joined together to evaluate the benefit of surgery as such in FAI treatment. The results were statistically analysed using the Wilcoxon test for paired samples; the level of significance was set at 0.05. RESULTS: There was a statistically significant increase in the scores obtained after surgery, as compared with the pre-operative data, in the SHD and AMIS groups and in all patients evaluated together. Hip survival without the necessity of conversion to total hip replacement was 96.4% (80/83 hips) in the SHD group and 94.1% (16/17 hips) in the AMIS group. no serious complications were recorded. DISCUSSIOn The rate of failure in the surgical treatment of FAI syndrome in our patients was in accordance with the literature data, as was the number of the patients requiring conversion to total hip replacement. Also the other results were comparable with those of relevant studies. CONCLUSIONS: Hip preservation surgery is an issue which has slowly been gaining consensus although opinions on it, including FAI surgical treatment, still vary. As FAI syndrome is a condition leading to degenerative changes in the hip, it is important to pay attention to a thorough diagnostic evaluation and a correct, though often long-term, therapy.
Keywords: Arthralgia; lidé; miniinvazivní chirurgické výkony; femoroacetabulární impingement; Humans; kyčel; Minimally Invasive Surgical Procedures; Femoracetabular Impingement; Hip; artralgie